Encontro nas águas: os vários sentidos do banho de rio em Manaus e suas relações socioambientais - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
This paper presents, through a qualitative research of ethnographic character, the historical, cultural and identity aspects related to the practice of the river and igarapé bath in the city of Manaus-AM and its connections with socio-environmental issues. The material produced with the research can be used as support for the (re) formulation of policies that work with the areas destined to this cultural and leisure tradition. Initially, a bibliographic study was done on historical aspects related to the practice of river bathing in the city. A public beach and a private beach, Praia da Ponta Negra and Praia Dourada respectively, were defined as a locus for the study. It presents a detailed description of the river bath while leisure on these two beaches. Semi-structured interviews were conducted with three (03) groups of subjects that have a direct relationship with the respective beaches: residents of Ponta Negra Beach; Public manager of the Ponta Negra Tourist Complex and owner of Praia Dourada and; Bathers and merchants from both beaches. It was sought to identify, through interviews and direct observation, the relationship of these subjects with the space they use, the significances that they give to the river bath practice, their motivations, what they like in those places and, if there is a relationship of care with the natural environment considering socio-environmental aspects. For this, a survey was carried out of several actions in favor of the environment as well as we raised some legal devices. From the understanding of the cultural and historical aspects of the practice of the river bath, information emerges beyond the possibility of (re) formulation of public policies, there also emerge possible actions that are designed to ensure that this practice is socio-environmentally correct, as well as, collaborate with conservation of these places. The results indicate that although there is a historically inefficient public action, the actions of these managers and of the population constitute a scenario that seems receptive to changes in order to conserve remaining rivers and streams.
Keywords: Banho de rio; Manaus; Etnografia; Sustentabilidade; CIÊNCIAS AGRÁRIAS